The Impact of AirAsia's Professional Training and Education and Other Factors on Customer Loyalty - Song, Ng Hee; Paul, Gadi Dung; Yisi, Lu; Jiarui, Ma; Zunqi, Ma; Sihao, Liu; Chauhan, Himanshi; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
AirAsia began operations in late 1996 and has emerged as Asia's foremost low-cost airline over the past two decades. Considering that airplanes are now the primary mode of travel, customer satisfaction with the airline's service is paramount. In this context, professional training and education is crucial. The main objective of this paper is to examine the relationships between professional training, education and talent customer satisfaction among AirAsia customers. Data will be collected and analyzed from 100 students and 100 community members to explore the impact of professional training and education on customer satisfaction, and to deepen the understanding of their relationship. This study highlights the significant role that professional education and training play in enhancing customer satisfaction which will eventually lead to customer experiences and loyalty